1997
DOI: 10.1094/pdis.1997.81.5.492
|View full text |Cite
|
Sign up to set email alerts
|

Nonpathogenic Fusarium oxysporum Strain Fo47 Induces Resistance to Fusarium Wilt in Tomato

Abstract: Nonpathogenic Fusarium oxysporum strain Fo47 controls the incidence of Fusarium wilt. Four bioassays in which a strain of the pathogen F. oxysporum f. sp. lycopersici and Fo47 were not in direct contact were developed to evaluate whether Fo47 could induce resistance to Fusarium wilt in tomato plants. Fo47 and the pathogen were separated either physically or in time. Bio-assays were carried out under hydroponic conditions (two bioassays), in potting mix, or in autoclaved soil. Strain Fo47 protected tomato again… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
124
0
5

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 183 publications
(133 citation statements)
references
References 34 publications
4
124
0
5
Order By: Relevance
“…Second, many rhizosphere microorganisms can induce a systemic response in the plant, resulting in the activation of plant defence mechanisms (Pieterse et al 2003). This capacity has been identified in a wide range of bacteria (Van Loon et al 1998;Haas and Défago 2005), including endophytes (Compant et al 2005) as well as saprophytic (Fuchs et al 1997), hyperparasitic (Woo et al 2006) and arbuscular mycorrhizal fungi (Pozo et al 2002). Induced systemic resistance (ISR) does not confer complete protection, but it does protect the plant from various types of phytopathogens (including root pathogens), without requiring direct interaction between the resistance-inducing microorganisms and the pathogen (Van Loon et al 1998;Zehnder et al 2001).…”
Section: Direct Positive Effects Of Rhizosphere Microorganisms On Thementioning
confidence: 99%
“…Second, many rhizosphere microorganisms can induce a systemic response in the plant, resulting in the activation of plant defence mechanisms (Pieterse et al 2003). This capacity has been identified in a wide range of bacteria (Van Loon et al 1998;Haas and Défago 2005), including endophytes (Compant et al 2005) as well as saprophytic (Fuchs et al 1997), hyperparasitic (Woo et al 2006) and arbuscular mycorrhizal fungi (Pozo et al 2002). Induced systemic resistance (ISR) does not confer complete protection, but it does protect the plant from various types of phytopathogens (including root pathogens), without requiring direct interaction between the resistance-inducing microorganisms and the pathogen (Van Loon et al 1998;Zehnder et al 2001).…”
Section: Direct Positive Effects Of Rhizosphere Microorganisms On Thementioning
confidence: 99%
“…F221-B was found to effectively reduce Fusarium root rot and wilt of 3 lettuce varieties in the range of 64-85.3% as well as to promote their growth and yield. So far, many reports have provided such an evidence of successfully using many strains of non-pathogenic F. oxysporum recovered from either diseased rhizosphere soil or suppressive soil for controlling soil-grown crops Fuchs et al 1997;Duijff et al 1998;Fravel et al 2003) but not in hydroponics. Fo47 is the best known and most effective nonpathogenic strain of F. oxysporum which was isolated from a soil naturally suppressive to Fusarium wilt of tomato and melon in France (Alabouvette 1990;Alabouvette & Couteaudier 1992;Alabouvette et al 1993Alabouvette et al , 1996Alabouvette et al , 1998Larkin & Fravel 1999) and has been extensively studied for the control of Fusarium wilt disease of several vegetables and flower crops such as tomato (Fuchs et al 1997(Fuchs et al , 1999Duijff et al 1998), carnation (Lemancean et al 1992, and flax (Duijff et al 1999).…”
Section: Discussionmentioning
confidence: 99%
“…This was in line with two findings when one demonstrated the ability of non-pathogenic F. oxysporum (V2w2 and III4w1) to penetrate the intact host tissue and recolonise the host internally upon inoculation in nutrient solution (Paparu et al 2006) and the other revealed the capability of non-pathogenic F. oxysporum in colonising the lower parts of plantlets such as roots (Olivain & Alabouvette 1999). The mechanism of action associated with nonpathogenic F. oxysporum can be divided into two broad categories: direct antagonism of non-pathogenic strains to the pathogen and indirect antagonism mediated through the host plant such as induced resistance (Fuchs et al 1997). The same non-pathogenic strain can express several modes of action either simultaneously or at different times.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…radicis lycopersici yang menyebabkan busuk akar dan pangkal batang pada tanaman tomat mampu dikendalikan melalui penambahan cendawan nonpatogenik F. oxysporum Fo47 ke dalam tanah. Inokulasi dengan Fo47 meningkatkan aktivitas kitinase, β-1,3-glucanase, dan β-1,4-glucosidase yang menginduksi ketahanan di dalam tanaman tomat (Fuchs et al 1997). Selain itu, cendawan Fusarium nonpatogenik diduga berpengaruh terhadap perkembangan Fusarium oxysporum patogenik yang disebabkan adanya kompetisi ruang dan waktu selama proses perkembangan cendawan.…”
Section: Korelasi Parameter Pengujian Blotter Test Dengan Tingkat Infunclassified